Self-reported worry and action among Vietnamese citizens during the COVID-19 pandemic in 2021: latent class analysis - Pham Quoc, Hung; Dao Anh, Son; Pham Anh, Tung (International Journal of Public Health Science (IJPHS), 2024)
Describe the prevalence of and factors associated with self-reported worry and actions of Vietnamese citizens during the COVID-19 pandemic in 2021. A secondary data analysis was implemented using a cross-sectional survey conducted in 2021 among 447 adults living in Hanoi City from July to December 2021 and Ho Chi Minh City from May to October 2021. The hidden layers assessment results retained the 3-class model as the best-fitting one in the study. In this model, 28.4% of participants were in Class 2 - "Low Self-reported Worry and Moderate Action" group, 45.9% of the participants were classified into Class 1-"Moderate Self-reported Worry and Low Action" group, and 25.7% in Class 3 - "High Self-reported Worry and High Action" group. The multinomial logistics model showed that worrying about losing the house because of COVID-19 makes the expected participation risk of staying in latent class 1 lower for subjects high in latent class 3 (p<0.05). Our study identified the latent classes of self-protection action and awareness among Vietnamese citizens. The associated factor that impacted the classes was the fear of losing a house.